The Implementation of Scout Education Management in Character Building of Gudep Students - Ade Irvan Margolang; Alamsyadana, Azwar; Silalahi, Khairul Amri; Syahbanda, M. Rezi; Pras, Jogi; Budi, Budi (The Future of Education Journal, 2025)
Scouting education management plays an important role in the formation of students' character, especially through the Scout Group (Gugus Depan) activities in schools. This study aims to analyze the implementation of scouting education management and its impact on the formation of students' character based on the Systematic Literature Review (SLR) approach and literature study. The SLR method is used to collect and evaluate literature related to the implementation of scouting management, while the literature study supports the analysis of relevant concepts and theories. The results of the study indicate that scouting education management includes planning, implementing, evaluating, and supervising structured scouting activities, with a focus on character values ​​such as discipline, responsibility, and leadership. These findings confirm that scouting education makes a significant contribution to the formation of students' character. This article provides strategic recommendations for optimizing Gudep management in supporting character education in schools.